The Roy adaptation model in the context of nursing models with examples of application and difficulties - Callista Roy (Universidad de Alicante, 2012)
In this work we will talk about nursing models in general. Secondly, I will describe the RAM specifically, including the philosophical and scientific assumptions as well as the key concepts. Thirdly, I will provide examples of applications of the model in practice and conclude with a discussion of some of the difficulties encountered when the model is used in practice and in nursing education. As models for nursing practice began to be developed in the United States in the 1970s and the 1980s, it was noted that looking across different models, we could find the same basic elements. Models include a clear concept of the person. Understanding the human person is based on our philosophy as well as our scientific view of persons and their place in the world around. In addition, nursing models in describing the world that people interact with are describing what we call environment. The other two major concepts are the notion of health and the idea of nursing itself. Nursing models then are depictions of nursing practice that are expressed using the essential concepts of person, environment, health, and nursing.